Visible Light Photocatalysis on Magnetically Recyclable Fe3O4/Cu2O Nanostructures - Pal S.; Kumar A.; Kumar S.; De A.K.; Prakash R.; Sinha I. (My University, 2025)
Abstract: Magnetically recyclable visible light photocatalysts for the degradation of critical organic pollutants are an urgent industrial requirement. Nonetheless, one component photocatalysts frequently suffer from photo corrosion and recombination issues. Constructing composites of a photocatalytic magnetic phase with a visible range semiconductor could solve both problems. The current article investigates the visible light photocatalytic effectiveness of starch stabilized Fe3O4/Cu2O nanostructures for photocatalytic degradation of p-nitrophenol (PNP) and methyl orange (MO). A stage-wise co-precipitation protocol was employed to prepare these nanocomposites. Mott-Schottky plots of these nanocomposites exhibited positive and negative slope parts, confirming the formation of a p-n heterojunction. Such a coupling of p-type Cu2O with n-type starch functionalized Fe3O4 resulted in a better photocatalyst with improved photostability. Both PNP and MO degradation followed zero-order kinetics under photocatalytic conditions. The nanocomposites demonstrated appreciably better visible light photocatalytic properties along with excellent recyclability. Graphical Abstract: [Figure not available: see fulltext.]Schematic representation of the mechanism proposed for explaining the photocatalytic Fenton degradation of organic pollutants. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.